Non-pressurized magnetorheological damper controlled using fuzzy semi active damping force estimator (fSADE) - Saiful Anuar, Abu Bakar; Hishamuddin, Jamaluddin; Roslan, Abd Rahman; Pakharuddin, Mohd Samin; Ryosuke, Masuda; Hiromu, Hashimoto; Takeshi, Inaba (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.